Inventory and Conservation of Triassic Vertebrate Tracks in the Monts d’Ardèche UNESCO Global Geopark, France - Emmanuel Fara; Jean-David Moreau; Leo Szewczyk; Nicolas Klee; Georges Gand; Emmanuelle Vennin (Geoconservation Research)
The Regional Natural Park (RNP) of the Monts d'Ardèche, located in south-eastern France, became the Monts d’Ardèche UNESCO Global Geopark in September 2014. This territory possesses significant geological structures, including numerous and rich Middle-Late Triassic vertebrate tracksites. The UNESCO Global Geopark label helped to formalize a long-standing partnership for the study of this ichnological patrimony between the RNP of the Monts d'Ardèche and the University of Burgundy. Developing scientific research, protection, training and outreach are the main lines of the agreement signed in 2015. The strategy is to make a detailed and sedimentologically contextualized inventory of vertebrate tracks in the Geopark and its surroundings, establish conservation and protection priorities, set up geosites for the public and involve local people in all these activities. To date, 15 tracksites and nearly a thousand individual tracks have been inventoried. The locality “Le Sartre” stands out as being the first recognized geosite amongst the remarkable tracksites in Ardèche. After four years of scientific investigations and fitting out works, it was inaugurated in October 2020. This geosite is the first equipped locality in France to show Late Triassic dinosaur tracks and to be freely accessible to the public. This success was made possible by the intellectual, logistic and social involvement of local people throughout, by acknowledgement of these contributions, and by the capacity of all actors to collaborate efficiently with each other. With more than 1000 fossil vertebrate tracks still awaiting to be valorized in Ardèche, the designation as a UNESCO Global Geopark clearly marked a turning point from academic-only to articulated research, conservation and geotouristic initiatives involving local communities.